THE IMPROVEMENT OF EXPRESSING CAUSAL CLAIM AND NEGATION SKILLS IN SOLUBILITY AND SOLUBILITY PRODUCT CONCEPT BY PROBLEM SOLVING LEARNING MODEL - nurma elisa; noor fadiawati; chansyanah diawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
The aim of this research is to describe effectiveness of problem solving learning model in solubility and solubility product concept to enhance expressing causal claim and negation skills. Students who became the subject of this research was  XI grade of Science 1 Batanghari Senior High School in Batanghari academic year 2011/2012. This research used the pre-experimental method and one group pretest-posttest design.  The effectiveness of problem solving learning model was determined based on the average value of n-Gain.  The results of this research showed that the average value of n-Gain of expressing causal claim and negation skills were 0,398 and 0,704. Thus, it can be concluded that the problem solvinglearning model in solubility and solubility product concept effective to enhance  expressing causal claim in medium category and effective to enhance  expressing negation skill in high category.Keywords: problem solving, expressing causal claim skill and expressing    negation skill.